2013
DOI: 10.2478/prge-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of intron sequence conservation in the genus Tetrahymena

Abstract: Background:Introns constitute a large fraction of eukaryotic genomes and were once considered neutrally evolving sequences. Recently, however, some introns have been found to harbor sequences that are involved in a variety of regulatory and other functions and show evidence of purifying selection. Results: We examine the pattern of sequence divergence among ciliates in the genus Tetrahymena. We find that on average introns are more highly conserved than four-fold degenerate sites. Among introns, we find a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Consistently, some studies have shown that intron divergence has a significant negative correlation with the length of first introns in Drosophila [ 27 , 37 ]. Zheng et al [ 38 ] have also reported that, in Tetrahymena , the most conserved introns are found closer to the 5’ end of genes. Furthermore, introns harboring regulatory elements tend to be the first introns [ 38 40 ], and, in fact, the frequencies of certain regulatory motifs are greater in first introns [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, some studies have shown that intron divergence has a significant negative correlation with the length of first introns in Drosophila [ 27 , 37 ]. Zheng et al [ 38 ] have also reported that, in Tetrahymena , the most conserved introns are found closer to the 5’ end of genes. Furthermore, introns harboring regulatory elements tend to be the first introns [ 38 40 ], and, in fact, the frequencies of certain regulatory motifs are greater in first introns [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [ 38 ] have also reported that, in Tetrahymena , the most conserved introns are found closer to the 5’ end of genes. Furthermore, introns harboring regulatory elements tend to be the first introns [ 38 40 ], and, in fact, the frequencies of certain regulatory motifs are greater in first introns [ 41 ]. Overall, it seems that, among the various possible roles of introns, first introns have especially evolved to harbor regulatory elements.…”
Section: Introductionmentioning
confidence: 99%